Peran Penyuluhh Pertanian Lapangan Pada Kelompok Tani Padi Sawah Di Desa Tombolango Kecamatan Sangkub Kabupaten Bolaang Mongondow Utara - Pontoh, Moh Hafiz; Tambas, Jane Sulinda; Porajow, Oktavianus (AGRI-SOSIOEKONOMI, 2023)
This study aims to find out how important the role of agricultural extension workers is in farmer groups, especially rice farmer groups. North Bolaang Mongondow Regency is the third largest producer of rice in North Sulawesi Province. This research was conducted in the Pangan Jaya rice farmer group with 10 farmer group members and the largest land area in Sangkub District, North Bolaang Mongondow Regency. This research was conducted from May to July 2022. The selection of respondents was intentional. Primary data is data obtained from respondent farmers through interviews using a questionnaire. Secondary data is data obtained from the Village office, Agriculture Office, Agricultural Extension Center, and other related agencies. The results showed the role of agricultural extension workers in the Pangan Jaya rice farmer group.